Interação do nitrogênio com o potássio na intensidade da ferrugem e da mancha aureolada do cafeeiro em solução nutritiva - Pérez, Cristian David Plaza (2015)
With the objective of evaluating the effect of nitrogen and potassium fertilization, two experiments were conducted, one in greenhouse and the other in a growth chamber, in order to evaluate the intensity of rust and bacterial blight, respectively. Both trials were conducted at the Department of Plant Pathology (DFP), of the Universidade Federal de Lavras (UFLA). We used the susceptible cultivar Mundo Novo 374/4. The treatments for both experiments were the same, consisting of five N doses (3, 7, 11, 15 and 19 mmol.L -1 ) in combination with five K doses (3, 5, 7, 9 and 11 mmol.L -1 ) in a 5 x 5 factorial scheme, totalizing 25 treatments and three replicates composed of two seedlings. The experimental design was completely randomized. In the first experiment (Rust), we observed a significant interaction between N and K for the area under the severity progress curve (AUDCPS) and dry weight of the leaves. There was no isolated or combined influence of N and K over the studied ecophysiological variables (Chlorophylls a, b and total and photosynthesis). In the second experiment (Halo blight), we observed significant difference only for N in AUDCPS, total dry matter and chlorophylls a, b and total. There was a significant positive correlation for chlorophylls a, b and total with N and the AUDPCS.